Determinants of student achievement in Botswana, South Africa and Zimbabwe : a multilevel approach - Ndlovu, Ntobeko (School of Economics, 2016)
An educated population has significant advantages relative to an uneducated one, since education has a high economic and social payoff. However, in the education process, scholars are not in agreement on which factors better explain student achievement. Some argue that school resources are key determinants, whereas other scholars maintain that factors outside the school better predict student achievement. Even within these sentiments, there are arguments on which school-level, classroom-level or student-level variables better explain achievement. Knowledge of such factors is critical, as it helps stakeholders to devise strategies that improve student success. It also helps to maximise budget allocations and at the same time gets the most out of per dollar expenditure. This study has used data from the Southern and Eastern Africa Consortium for Monitoring Educational Quality (SACMEQ III) to estimate the determinants of student mathematics achievement in three developing countries in Southern Africa; namely, Botswana, South Africa and Zimbabwe.